Creating the Perfect Vibe: How Café Atmosphere Drives Customer Repurchase Intentions - Siallagan, Andrew Henradoth Grimaldi; Putri, Yulia; Iisnawati, Iisnawati (Studi Ilmu Manajemen dan Organisasi, 2025)
Purpose: This study aims to analyze the impact of Store Atmosphere on Repurchase Intention at Pojok Kopi Café in Indralaya. This study seeks to enhance the understanding of how different dimensions of the store environment influence customers' intentions to make repeat purchases. This study aims to provide valuable insights that can be applied practically and contribute to academic knowledge in the fields of Store Atmosphere and Repurchase Intention. Methodology/approach: This research was conducted at Kafe Pojok Kopi, Indralaya involving 100 respondents as the object of study. This study also uses quantitative methods and is analyzed using Multiple Linear Regression. Results/findings: This study found that Cleanliness, Music, Temperature, and Layout significantly affect Repurchase Intention. Scent, lighting, and color do not significantly influence Repurchase Intention. Store Atmosphere significantly influences Repurchase Intention. Conclusion: The study found that cleanliness, music, temperature, and layout significantly affect repurchase intention at Kafe Pojok Kopi, while aroma, lighting, and color do not. Future research should include factors such as price, location, and service to provide broader insights. Limitations: Other variables should be considered in future studies to address the problems that are the background of this study, such as price. This is because the results of the study could not answer the background of this study. Contribution: This study aims to guide Café Pojok Kopi in innovating its store atmosphere and illustrates how the store environment significantly influences repurchase intentions. The findings will support practical applications and academic advancements in this area.